1988
DOI: 10.1002/j.1460-2075.1988.tb03074.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of beta-tubulin isotypes in cerebellum.

Abstract: We describe the structure and expression of a mammalian beta‐tubulin isotype (M beta 6) that is weakly expressed in testis but is abundant in developing brain, with transcripts declining to lower levels in the adult brain. The expression of M beta 6 was undetectable in any other mouse tissue examined. A serum specific for this isotype was prepared using a cloned fusion protein as immunogen. M beta 6 is one of five known beta‐tubulin isotypes expressed in brain, and using the anti‐M beta 6 serum along with sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
97
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 42 publications
5
97
0
Order By: Relevance
“…Our results also indicated that class II was a major component in the brain and classes III and IVa were brain-specific. These results are consistent with previous reports [2,24,25]. Furthermore, it was shown that the class IVb isotype accounts for about 90% of testis β-tubulin.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results also indicated that class II was a major component in the brain and classes III and IVa were brain-specific. These results are consistent with previous reports [2,24,25]. Furthermore, it was shown that the class IVb isotype accounts for about 90% of testis β-tubulin.…”
Section: Discussionsupporting
confidence: 94%
“…To the best of our knowledge, this is the first report on the RPA of the expression levels of mRNA coding for β-tubulin isotypes. A differential distribution of each isotype was shown in murine tissues by northern blotting [2] but, the method could not distinguish class IVa from class IVb, since these isotypes closely resemble each other in nucleotide sequence and size. Therefore, recent studies on the mRNA expression levels of each isotype have employed PCR-amplification procedures [12,16,21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Class I (Constitutive; Human h␤1) ␤I EEEEDFGEEAEEEA Class II ('Major brain' or 'major neuronal') ␤II DEQGEFEEEEGEDEA Class III ('Minor brain' or 'minor neuronal'; Human h␤4) ␤III EEEGEMYEDDDEESEAQGPK Class IVa ('Brain specific'; Human ␤5) ␤IVa EEGEFEEEAEEEVA Class IVb ('Major testis'; Human h␤2) ␤IVb EEEGEFEEEAEEEVA Class V ('Avian specific'; Chick c␤5) ␤V NDGEEAFEDEDEEEEINE Class VI ('Hematopoietic') ␤VI GLEDSEEDAEEAEVEAEDKDII al., 1982;Dietrich et al, 1987;Burgoyne et al, 1988;Caccamo et al, 1989a;Moody et al, 1989;Lee et al, 1990a,b;Easter et al, 1993;Katsetos et al, 1993;Ludueña, 1998;Farina et al, 1999;Modig et al, 1999]. However, ␤III protein is not detectable in the developing or mature Xenopus nervous system.…”
Section: Table I ␤-Tubulin Isotypesmentioning
confidence: 99%
“…Of these, only one, ␤III, also known as the "minor neuronal isotype," human h␤4 or mouse m␤6, appears to be expressed almost exclusively by neurons [Sullivan and Cleveland, 1986;Burgoyne, 1988;Sullivan, 1988;Moody et al, 1989;Lee et al, 1990b;Easter et al, 1993;Ludueña, 1998]. In contrast, the ␤II ("major neuronal") and ␤IVa ("brain-specific") isotypes are normally distributed in both neurons and glia.…”
Section: Table I ␤-Tubulin Isotypesmentioning
confidence: 99%